London's late night scandal - Bryant, Anabelle (Bryant, Anabelle. Midnight secrets., 2019)
Chief Officer of the Society for the Intellectually Advanced, Lord Matthew Strathmore, Earl of Whittingham, takes his position very seriously. Not only does it distract him from the painful aftermath of a gunshot wound to the leg, earned most honorably, it is important work. So he feels duty-bound to question esteemed scientist Lord Talbot about a suspect article. Matthew dashes from London to Oxfordshire, despite wretched weather that only exacerbates his injury, reminding him he is far from the dashing gentleman he once was . . . Theodosia, Lord Talbot<U+2019>s granddaughter, has inherited his gift for inquiry, enjoying her pursuits safely away from the artifice of London society. But her identity as the true author of Talbot<U+2019>s article is about to be exposed. And if Matthew expects a dour bluestocking, surprises abound. Not only do Theodosia<U+2019>s botanical concoctions soothe his leg, he<U+2019>s clearly attracted by her delicate beauty. But dare she hope for more? It will take an urgent trip to London for both to discover how passion and lasting love can ignite under the cover of darkness . . .